Cooperative Scripts Model in Civic Education for Elementary School Students - Indriani, Dian Eka (Bina Nusantara University, 2017)
The purpose of this research was to eliminate misconceptions and increase the level of students? comprehension on Civic Education subject cultural diversity in Indonesia matters. The research applied a quasi-experimental method. The respondents were 25 students of SDN Muhammadiyah 1 Banyuajuh, Malang. Data were analyzed descriptively qualitative and quantitative. The results show valid learning materials, activity on student-centered, teaching and learning materialized well (3,9). The result of students? concept comprehension has been analyzed by N-Gain that shows improvement (0,75), and students? misconception is decreasing. It can be said that the Cooperative Scripts learning materials are feasible, has influence, and can enhance the concept comprehension and significantly affect the elimination of students? misconception on Civic Education subject in Elementary school students.